2017
DOI: 10.21037/atm.2017.03.31
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of exon 11 mutants in GIST treated with standard dose Imatinib

Abstract: Background: The exon 11 KIT mutant gastrointestinal stromal tumors (GIST) is a heterogeneous cohort with variable biological behavior based on different mutational subtypes. Methods:Patients with histologically proven GIST with KIT exon 11 mutations were selected from a prospectively maintained database, and evaluated for clinical characteristics and event free survival (EFS). Patients were divided into mutations upstream to codon 557 (G1), mutations involving codon 557-558 (G2) and mutation downstream to codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In patients with early detection of exon 11 mutations, a low dose of imatinib (400 mg/day) is adequate (11,13,35). Ramaswamy and colleagues showed that CD117 exon 9 mutations have 38 months of overall survival compared to CD117 exon 11 mutation with a survival rate of 66 months (36). Patients with exon 13 or 14 mutations benefit from sunitinib and exon 17 mutations benefit from ponatinib ( Table 6) (11)(12)(13).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…In patients with early detection of exon 11 mutations, a low dose of imatinib (400 mg/day) is adequate (11,13,35). Ramaswamy and colleagues showed that CD117 exon 9 mutations have 38 months of overall survival compared to CD117 exon 11 mutation with a survival rate of 66 months (36). Patients with exon 13 or 14 mutations benefit from sunitinib and exon 17 mutations benefit from ponatinib ( Table 6) (11)(12)(13).…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…Accumulative evidence suggests the effectiveness of imatinib in both the adjuvant and metastatic GISTs in patients with KIT or PDGFRA mutations [ 64 , 65 , 66 , 67 ]. However, imatinib was not effective in all patients, because it was found that GIST patients with mutations in the exon 9 of the KIT gene have lower effectiveness compared to mutations in exon 11 [ 41 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since exon-11-mutant KIT GIST is heterogeneous, it was advisable to plan treatment strategies based on individual mutant cohorts [68] . Imatinib can improve the prognosis of advanced GIST patients [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations